2019
DOI: 10.1093/toxsci/kfz068
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin Inhibits L-Type Ca2+-Channel Activity Through Impairment of Mitochondrial Function

Abstract: Plasma membrane ion channels and mitochondrial electron transport complexes (mETC) are recognised "off-targets" for certain drugs. Simvastatin is one such drug, a lipophilic statin used to treat hypercholesterolaemia, but which is also associated with adverse effects like myopathy and increased risk of glucose intolerance. Such myopathy is thought to arise through adverse actions of simvastatin on skeletal muscle mETC and mitochondrial respiration. In this study we investigated whether the glucose intolerance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 46 publications
0
6
0
2
Order By: Relevance
“…More recently, it has been suggested that statins can reduce the membrane potential by inhibiting mitochondrial complex II activity, which causes oxidative stress [74]. These off-target effects of statins have been very recently corroborated by Curry et al [75] in experiments showing that simvastatin impairs β-cell function by at least two mechanisms: (1) via direct inhibition of K ATP channels in a mitochondria-independent manner and (2) via interference with mitochondrial respiration, thus decreasing cytosolic ATP levels and inhibiting metabolic upregulation of L-type Ca 2+ channels [75].…”
Section: Dysfunctional Effects Caused By Statins In Pancreatic β-Cellmentioning
confidence: 91%
“…More recently, it has been suggested that statins can reduce the membrane potential by inhibiting mitochondrial complex II activity, which causes oxidative stress [74]. These off-target effects of statins have been very recently corroborated by Curry et al [75] in experiments showing that simvastatin impairs β-cell function by at least two mechanisms: (1) via direct inhibition of K ATP channels in a mitochondria-independent manner and (2) via interference with mitochondrial respiration, thus decreasing cytosolic ATP levels and inhibiting metabolic upregulation of L-type Ca 2+ channels [75].…”
Section: Dysfunctional Effects Caused By Statins In Pancreatic β-Cellmentioning
confidence: 91%
“…Since, the release and action of S100β are calcium-dependent, mainly cytosolic ca + 2 , a recent work illustrated that simvastatin inhibits cytosolic ca + 2 in AIS, thereby may inhibits the release of S100β from ischemic neurons. [ 43 ] Indeed, statins inhibit acute activation of astrocyte cells in AIS, and other modalities of brain injury and prevent astrocyte cells for synthesis of new S100β. [ 44 ] These findings, might explain the low level of S100β in patients with AIS on statins therapy compared with nonstatins therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Ймовірно, що інгібітори ГМГ-КоАредуктази здатні знижувати мембранний потенціал, пригнічувати активність мітохондріального комплексу II, що зумовлює ОС [45]. Ці нецільові ефекти інгібіторів ГМГ-КоАредуктази підтверджені експериментально, зокрема, показано, що симвастатин змінює функцію β-клітин, принаймні, через два механізми: (1) шляхом прямого інгібування АТФзалежних калієвих каналів і (2) шляхом втручання в мітохондріальне дихання -внаслідок зниження рівня цитозольного АТФ і пригнічення активності Са 2+ -каналів L-типу [46].…”
Section: наслідки Consequencesunclassified